Strategi Food Estate Sebagai Solusi Keamanan Pangan - Alifya, Hafizha; Silvya Sari, Deasy; Yulianti, Dina (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The Indonesian government is committed to maintaining food security, one of which is through the implementation of the food estate program as part of strategic policies. Causal Loop Diagram and Stock and Flow Diagram in The System Dynamics method is used to analyze the relationship between food estate variables and food safety. The model used focuses on looking at the relationship between land targets and the time or year of the food estate policy program. The purpose of this study is to find out about the success of the land target set in the food estate program. The results are then analyzed according to the condition of food estate in Indonesia. Suggestions and recommendations are given regarding the implementation of the food estate system to achieve food security.